Bronchial anastomotic complications as a microvascular disruption in a mouse model of airway transplantation - Khan, Mohammad Afzal; Bhusal, Subarna; Lau, Christine L.; Krupnick, Alexander Sasha (Frontiers in Immunology, 2025)
Lung transplantation (LTx) offers a last resort for patients battling end-stage lung disease. Even though short-term survival has improved, these patients still face several long-term challenges, such as chronic rejection and ischemic bronchial anastomosis. In lung transplant recipients, the bronchial anastomosis is prone to complications—such as poor wound healing, necrosis, stenosis, and dehiscence—due to the marginal blood supply at this site. During peri-LTx, hypoxia and ischemia stimulate fibrotic and inflammatory cytokines at anastomotic sites, leading to abnormal collagen production and excessive granulation, which impair wound healing. Despite meticulous techniques, bronchial anastomosis remains a major cause of morbidity and mortality among lung transplant recipients. After LTx, most bronchial complications are attributed to ischemic insult since normal bronchial blood flow is disrupted, and bronchial revascularization usually takes two to four weeks, making the anastomotic bronchial vessels dependent on pulmonary artery circulation. It is clear that hypoxia, inflammation, oxidative stress, and extracellular matrix remodeling play critical roles in bronchial complications, but there is no small animal model to study them. In the context of LTx, mouse tracheal models are essential tools for studying bronchial complications, particularly ischemia, fibrosis, and stenosis, as well as evaluating potential therapeutic interventions. A well-established mouse model of orthotopic tracheal transplantation (OTT) mimics the anastomosis of the bronchi and the subsequent microvascular injury, providing a pathological correlation with anastomotic complications. A series of previous studies using the OTT model explored the microvascularization, ischemia-reperfusion, airway epithelial injury, and fibrotic remodeling effects after airway anastomosis. This review describes OTT as a model of airway anastomotic complications, which is crucial for understanding the immunological and molecular pathways as seen in clinical bronchial anastomoses, as well as improving anastomotic healing and reducing complications through targeted therapeutic strategies.